Transesterification of Rice Bran Oil Using Biocatalyst - Verma, Atish (My University, 2012)
The work presents the findings on the whole cell catalyzed transesterification of used-rice bran oil with dry biomass of Aspergillus species. The effect of chain length of alcohol on the extent of transesterification was examined using primary and other alcohols as acyl donors. The results indicated that increase in chain-length significantly favours the reaction towards enhanced yield of alkyl esters especially with acyl donors ranging from butanol to heptanol. The study also resulted in deriving an equation for the NMR based quantification of alkyl esters, generated through transesterification of oil using primary alcohols beyond ethanol. The results obtained through the modified equation significantly correlated with the yield of alkyl esters determined through GC analysis.
M.Sc. (Chemistry)
Keywords: Biomass; biocatalyst; lipase; biodiesel; enzyme